Magnetic field assisted melt–spinning Nd-Fe-B ribbons and anisotropic bonded NdFeB magnets prepared thereof - Truong, Nguyen Xuan; Vuong, Nguyen Van (Communications in Physics, 2016)
The magnetic-field-assisted melt-spinning (FAMS) Nd10.5Fe72Co11B6.5 ribbons were spun in an external magnetic field of 3 kG. The prepared ribbons were ball-milled in xylene solvent for 30 minutes followed by adding in and mixing with the high-temperature binder HTB-1 (3 wt%) for further 10 minutes. The mixed powder was dried and in-mold aligned in a magnetic field of 18 kOe and hot-compacted at 200 oC. The parameters of the FAMS ribbon preparation, ball-milling process, hot-compaction and anisotropic bonded magnets’ fabrication were optimized leading to the magnet’s energy product (BH)max of 10 MGOe. The microstructure and magnetic properties of prepared ribbons and bonded magnets will be discussed in details.